2000
DOI: 10.1109/58.818767
|View full text |Cite
|
Sign up to set email alerts
|

Novel concepts for GaAs/LiNbO/sub 3/ layered systems and their device applications

Abstract: Thin semiconductor quantum well structures fused onto LiNbO(3 ) substrates using the epitaxial lift-off (ELO) technology offer the possibility of controlling the surface acoustic wave (SAW) velocity via field effect. The tunability of the conductivity in the InGaAs quantum well results in a great change in SAW velocity, in general, accompanied by an attenuation. We show that an additional lateral modulation of the sheet conductivity reduces the SAW attenuation significantly, enhancing device performance. At hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Analogously, changes of the charge conductivity in a 2-dimensional electron gas (2DEG) modify the SAW device performance. For practical applications, materials with a large K 2 are needed, like hybrid AlGaAs/GaAs/LiNbO 3 structures [39] or ZnO/MgZnO quantum wells on sapphire substrates [40], in which external voltages are applied by split gates. In these cases, SAWs travel through the 2DEG, though the input and output IDTs must be deposited on nonconductive material, thus requir-…”
Section: Integration Of Saw With 2degmentioning
confidence: 99%
“…Analogously, changes of the charge conductivity in a 2-dimensional electron gas (2DEG) modify the SAW device performance. For practical applications, materials with a large K 2 are needed, like hybrid AlGaAs/GaAs/LiNbO 3 structures [39] or ZnO/MgZnO quantum wells on sapphire substrates [40], in which external voltages are applied by split gates. In these cases, SAWs travel through the 2DEG, though the input and output IDTs must be deposited on nonconductive material, thus requir-…”
Section: Integration Of Saw With 2degmentioning
confidence: 99%
“…For this purpose, one can place between IDTs a semiconductor film with low voltage-controlled sheet conductivity. 17…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have reported on SAW devices using two-dimensional electron gas (2DEG) heterostructures, mainly AlGaAs/ GaAs on top of a strong piezoelectric substrate like LiNbO 3 (hybrid systems) [6,7] or MgZnO/ZnO quantum wells grown on sapphire substrates [8].…”
Section: Introductionmentioning
confidence: 99%
“…In [6], a more general model of left-handed transmission line metamaterials, composite right/left-handed (CRLH) transmission line, was proposed. Various types of applications based on left-handed TLs and CRLH TLs have been proposed, such as some couplers [7,8], leaky wave antennas [9,10], and filters [11].…”
Section: Introductionmentioning
confidence: 99%